Finding Legitmacy on European Union Trade Policy to Limit the Import of Palm Oil: Will Indonesia Survive (again)? - Sutrisno, Nandang (UI Scholars Hub, 2019)
In March 2019, the European Union considered palm oil to cause ILUC along with being one of the contributors for emission and pollution. However, the move has been condemned by palm oil exporting States, such as Indonesia. It is accused as a modern, “green protectionist” move to protect national market or other countries importing goods. Since European Union uses environmental justification to restrict palm oil import from Indonesia, it is inherently correlated with the general exception enshrined in Article XX of the GATT relating to the principles of international trade. Under the assessment based on Article XX and judicial decisions before the WTO, the article concludes that the DR is not the only measure possible and will not give siginificant effect on ILUC. It only creates unjustifiable and arbitrary discrimination towards Indonesia since there is no sufficient link between the environmental purpose of the DR and its provisions